Estimación de reservas y elección de la mejor alternativa en la explotación de Caolín en la concesión minera Los Cruceros, del barrio Cola, parroquia Guachanama, cantón Paltas de la provincia de Loja. - Condoy Hurtado, Henry (2005)
The area of Cola, the cruises and neighboring sectors have been previously studied by the Ecuadorian-Australian company "ECUAZAR" in the exploration of metallic minerals with satisfactory results, the mining company "ELIPE SA" is currently carrying out advanced exploration studies, , But studies for the exploration of non-metallic minerals do not exist, referring to gypsum, kaolins, feldspars, limestones, so it was necessary to carry out this study in detail, complementing it with exploratory works that allow us to know its true mining potential. In the geological chart of Cariamanga scale 1: 100,000 edited by INEMIN "1973" a brief reference is made to the existence of kaolins, gypsum, and limestone; The same that served as a base to continue with the studies in its different phases of the mineralized body. The "Caolines Los Cruceros" association itself has exploited the Kaolin mantles in handmade form and has been marketed from time to time with the ceramic factories